Study of Fraud in Management of Fixed Assets at PT Makassar New Port - Hanafi, M. Raihan Wafil Amin; Majid, Jamaluddin; Aditya, Roby (Universitas Negeri Makassar, 2023)
Abstract. This study aims to determine the application of the shiddiq trait in minimizing fraud against fixed asset managers at PT Makassar New Port. This study uses a qualitative method with a phenomenological approach. The data sources in this study are primary data sources obtained from several informants and the results of field observations. The data collection method was carried out by conducting structural interviews, observation, and documentation with informants who were used as research subjects. The data analysis used is descriptive qualitative by looking at how the shiddiq trait is applied in minimizing fraud against fixed asset managers at PT Makassar New Port. Furthermore, the validity test of the data used includes trust, transferability, dependability and certainty. The results of this study indicate that the application of shiddiq traits in PT Makassar New Port for fixed assets is good and well implemented. This can be seen from the commitment of employees to carry out indicators of shiddiq traits in their daily activities, for example by maintaining honesty, adjusting their words and actions, being careful be careful in speaking, and be careful in making decisions. With shiddiq, it will produce financial reports that are reliable, transparent, trustworthy, and recorded according to what already exists so that fraud can be minimized. Keywords: Siddiq's Nature, Fixed Asset Manager, Fraud. Abstrak. Penelitian ini bertujuan untuk mengetahui penerapan sifat shiddiq dalam meminimalisir fraud terhadap pengelola aset tetap pada PT Makassar New Port. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Adapun sumber data yang dalam penelitian ini adalah sumber data primer yang diperoleh dari beberapa informan dan hasil observasi lapangan. Metode pengumpulan data dilakukan dengan melakukan wawancara struktur, observasi, dan dokumentasi dengan informan yang dijadikan subjek penelitian. Analisis data yang digunakan adalah deskriptif kualitatif dengan melihat bagaimana penerapan sifat shiddiq dalam meminimalisir fraud terhadap pengelola aset tetap pada PT Makassar New Port. Selanjutnya, uji keabsahan data yang digunakan meliputi kepercayaan, keteralihan, kebergantungan dan kepastian. Hasil penelitian ini menunjukkan bahwa penerapan sifat shiddiq dalam PT Makassar New Port untuk bagian aset tetap sudah bagus dan diterapkan dengan baik hal ini dilihat dari komitmen karyawan menjalankan indikator sifat-sifat shiddiq dalam aktivitas kesehariannya misalnya dengan menjaga kejujuran, menyesuaikan perkataan dan perbuatannya, hati-hati dalam berucap, dan hati-hati dalam mengambil keputusan. Dengan adanya shiddiq akan menghasilkan laporan keuangan yang handal, trasnparan, bisa dipercaya, dan dicatat sesuai yang sudah ada sehingga bisa meminimalisir tindakan fraud. Kata Kunci: Sifat Shiddiq, Pengelola Aset Tetap, Fraud